2018
DOI: 10.1017/s0967199418000102
|View full text |Cite
|
Sign up to set email alerts
|

Urea changes oocyte competence and gene expression in resultant bovine embryo in vitro

Abstract: SummaryNutrition influences the microenvironment in the proximity of oocyte and affects early embryonic development. Elevated blood urea nitrogen, even in healthy dairy cows, is associated with reduced fertility and there is high correlation between blood urea levels and follicular fluid urea levels. Using a docking calculation (in silico), urea showed a favorable binding activity towards the ZP-N domain of ZP3, that of ZP2, and towards the predicted full-length sperm receptor ZP3. Supplementation of oocyte ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
(85 reference statements)
0
10
0
2
Order By: Relevance
“…For example, we reported that high levels of urea disrupted the oviduct epithelial cell monolayer and reduced the viability of bovine cumulus cells [15][16][17] . We also documented that urea-incubated oocytes had a lower rate of developmental competence and higher more amino acid depletion during in vitro maturation (IVM) 17,18 . It has been shown that urea uses EGFR transactivation and induces the expression of immediate-early genes 19 and, as a toxic molecule, can induce ROS production in a variety of cells, such as oocytes 20 .…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…For example, we reported that high levels of urea disrupted the oviduct epithelial cell monolayer and reduced the viability of bovine cumulus cells [15][16][17] . We also documented that urea-incubated oocytes had a lower rate of developmental competence and higher more amino acid depletion during in vitro maturation (IVM) 17,18 . It has been shown that urea uses EGFR transactivation and induces the expression of immediate-early genes 19 and, as a toxic molecule, can induce ROS production in a variety of cells, such as oocytes 20 .…”
mentioning
confidence: 89%
“…Cumulus-oocyte complexes (COCs) with at least five cell layers were selected using a stereomicroscope (Olympus, Tokyo, Japan) and transferred to HEPES-TCM-199 supplemented by 50 mg/ml of kanamycin and 50 mg/ml of heparin. Intact COCs were then washed twice in HEPES-TCM199 and randomly put in groups of 10 in 50-µl droplet of maturation medium containing bicarbonate-buffered TCM199 supplemented by 10% 17,18 . After IVM, approximately 600 COCs (from 60 cows) were assigned to different treatments: (1) the control group in which oocytes were inseminated by untreated sperm cells (n = 140 oocytes, through 10 replicates, each replication (drop) containing 10-15 oocytes); (2) the EGF group in which oocytes were inseminated by sperm cells pre-treated with 10 ng/ml EGF for 30 min (n = 150 oocytes, 10 replicates, each replicate (drop) containing 10-15 oocytes); (3) the urea group in which oocytes were inseminated by sperm cells pre-treated with 40 mg/dl urea (equivalent to 18.7 mg/dl BUN) for 30 min (n = 150 oocytes in 10 replicates, each replicate (drop) containing 10-15 oocytes); and (4) EGF-urea group in which oocytes were inseminated by sperm cells pre-treated with a mixture of 40 mg/dl of urea and 10 ng/ml of EGF for 30 min (n = 160 oocytes in 10 replicates, each replicate (drop) containing 10-15 oocytes).…”
Section: Cumulus-oocyte Complex Collection and In Vitro Embryo Producmentioning
confidence: 99%
“…We have previously reported that high urea levels not only increased the percentage of oocyte degeneration, but also decreased the in vitro viability of CCs and oviduct epithelial cells 16,17,39 . In this study, the addition of urea to the maturation medium increased the percentage of oocyte degeneration by day 3 after insemination.…”
Section: Discussionmentioning
confidence: 90%
“…www.nature.com/scientificreports/ RNA extraction, reverse transcription, quantitative analysis of transcripts using qRT-PCR. RNA extraction and reverse transcription were conducted as reported earlier 16 . In short, total RNA was extracted from day-7 blastocysts using RNeasy Micro kit (Qiagen, Mississauga, Ontario, Canada) and then treated with DNase I (Ambion, Streetsville, Ontario, Canada) according to the manufacturer's manual.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation